1985
DOI: 10.1093/infdis/152.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Rotaviruses by Nucleic Acid Hybridization with Cloned DNA of Simian Rotavirus SA11 Genes

Abstract: We developed a dot-blot hybridization assay to detect rotaviral RNA sequences in tissue culture or in clinical samples. 32P-labeled cloned cDNA probes of the simian rotavirus SA11 specifically detected rotaviral RNA sequences and were more sensitive for detecting SA11 than was the commercial enzyme-linked immunosorbent assay Rotazyme test. A full-length probe of SA11 gene 6 detected 2.5 X 10(5) SA11 particles or approximately 0.27 ng of purified SA11 dsRNA. Combined probes from genes 6 and 9 detected 0.135 ng … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 15 publications
0
36
0
Order By: Relevance
“…Various methods to detect rotavirus or rotavii-al proteins in infected cell cultures have been developed and include a collodial gold-protein A-IgG technique (289), a radioimmunofocus assay (220), and an immunoperoxidase procedure (44). More recently, several sensitive and specific research techniques for the detection of rotavirus in clinical specimens have been developed, which include a dot-immunobinding assay (299), a dotavidin-biotin-amplified immunobinding assay (299), an avidin-biotin RIA (407), and several dot hybridization techniques (82,100,116,217 (155,159) found that the immunoglobulin secretory component (ScIg) increased in serum 1 to 2 weeks after disease onset; however, it had disappeared by 4 months. Grauballe et al (129) detected sIgA in patient sera for only 4 to 10 days after rotavirus was detected in stools, and this correlated well with recent infection.…”
Section: Epidemiologymentioning
confidence: 99%
“…Various methods to detect rotavirus or rotavii-al proteins in infected cell cultures have been developed and include a collodial gold-protein A-IgG technique (289), a radioimmunofocus assay (220), and an immunoperoxidase procedure (44). More recently, several sensitive and specific research techniques for the detection of rotavirus in clinical specimens have been developed, which include a dot-immunobinding assay (299), a dotavidin-biotin-amplified immunobinding assay (299), an avidin-biotin RIA (407), and several dot hybridization techniques (82,100,116,217 (155,159) found that the immunoglobulin secretory component (ScIg) increased in serum 1 to 2 weeks after disease onset; however, it had disappeared by 4 months. Grauballe et al (129) detected sIgA in patient sera for only 4 to 10 days after rotavirus was detected in stools, and this correlated well with recent infection.…”
Section: Epidemiologymentioning
confidence: 99%
“…Probes to the herpes viruses (2,3,13,16,20,54,74,88,103,115,122,125,126,143), adenoviruses (71,90,142), enteroviruses (58,108,109), reoviruses (26), hepatitis viruses (6,8,9,67,114), papillomaviruses (5,96), papovaviruses (44), and parvoviruses (22) have all been described.…”
Section: Definitionsmentioning
confidence: 99%
“…The cDNA probe was able to detect 50 ng of TRV dsRNA. The sensitivity reported for rotavirus probes in this type of assays is in the range of 0.5 to 5 ng of RNA (Dimitrov et al 1985, Eiden & Yolken 1987. We are attempting to improve the sensitivity of the cDNA probe by increasing the specific activity of the cDNA and by using highly specific RNA probes as described by Kreig & Melton (1984).…”
Section: Discussionmentioning
confidence: 89%